Exequibility of differential gene expression analysis by DDRT-PCR in murine bone marrow cells - De Almeida, Danilo C.; Santos, Rodrigo Da S.; Ribeiro-Paes, João T. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2012)
Model of study: Experimental study. Introduction: Recently, stem cell research has generated great interest due to its applicability in regenerative medicine. Bone marrow is considered the most important source of adult stem cells and the establishment of new methods towards gene expression analysis regarding stem cells has become necessary. Thus Differential Display Reverse Transcription Polymerase Chain Reaction (DDRT-PCR) may be an accessible tool to investigate small differences in the gene expression of different stem cells in distinct situations. Aim: In the present study, we investigated the exequibility of DDRT-PCR to identify differences in global gene expression of mice bone marrow cells under two conditions. Methods: First, bone marrow cells were isolated fresh and a part was cultivated during one week without medium replacement. Afterwards, both bone marrow cells (fresh and cultivated) were submitted to gene expression analyses by DDRT-PCR. Results: Initially, it was possible to observe in one week-cultured bone marrow cells, changes in morphology (oval cells to fibroblastic-like cells) and protein profile, which was seen through differences in band distribution in SDS-Page gels. Finally through gene expression analysis, we detected three bands (1300, 1000 and 225 bp) exclusively expressed in the fresh bone marrow group and two bands (400 and 300 bp) expressed specifically in the cultivated bone marrow cell group. Conclusions: In summary, the DDRT-PCR method was proved efficient towards the identification of small differences in gene expression of bone marrow cells in two defined conditions. Thus, we expect that DDRT-PCR can be fast and efficiently designed to analyze differential gene expression in several stem cell types under distinct conditions.
Keywords: Bone Marrow Cells; DDRT-PCR; Gene Expression; animal cell; bone marrow cell; cell culture; cell isolation; cell structure; differential display reverse transcription polymerase chain reaction; fibroblast; gene expression; gene expression profiling; mouse; nonhuman; polyacrylamide gel electrophoresis; reverse transcription polymerase chain reaction